ANALISIS KONDISI FISIK WASIT SEPAK BOLA KABUPATEN LUWU TAHUN 2022 - Arazzaq Fedra; Etno Setyagraha; Abdul Rahman (Jurnal Ilara : Jurnal Hasil Penelitian, Aplikasi Teori, Analisa, Dan Pembahasan Kepustakaan tentang Keolahragaan, 2023)
In a football match there is a referee who acts as a referee and leads the way of a football match. Therefore, a football referee must have a good physical condition will be able to display the referee's performance well to the maximum in making a decision when presiding over a match. This study aims to determine the physical condition of the Luwu district soccer referee in 2022. This research is a quantitative descriptive study using the test method, the instrument used from the FIFA High Intensity Interval Training (HIIT) namely: 6 x 40 meter sprint and run interval 40 x 75 meters/walk 25 meters to measure running speed and cardiovascular endurance. The sample used in this study amounted to 8 people. The data analysis technique used in this research is descriptive and percentage. The results of the research on the physical condition of the Luwu Regency soccer referee in 2022 in the element of speed, namely the less category (0%) with 0 respondents, in the good category (12.5%) with 1 respondent and in the very good category (87.5%) with 7 respondents. And the results of research on the physical condition of the Luwu Regency soccer referee in 2022 in the element of endurance, namely the less category (62.5%) with 5 respondents, in the good category (0%) with 0 respondents and in the very good category (37.5%) with 3 respondents. It can be concluded that the physical condition of the Luwu district soccer referee in 2022 on the element of speed is in the very good category, and on the element of endurance it is in the less category